Optimasi Waktu Maserasi untuk Manggis (Garcinia mangostana L.) Rind Menggunakan Pelarut Etil Asetat - Ni Putu Ayu Dewi Wijayanti; Dewi LPMK; Astuti KW; Fitri NPE (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2016)
Background: Maceration is a non-heating extraction method the result of which is affected by the type of solvent and the maceration time. Objective: To get the higher alpha-mangostin concentration (Garcinia mangostana L.) rind that was macerated using ethyl acetate solvent and to determine the optimum maceration time needed to produce high concentration of alpha-mangostin. Methods: the mangosteen rind was macerated using ethyl acetate with the variation of the maceration time of 6, 12, 24 and 48 hours. The extract was then dried using the freeze drying method. The optimum maceration time was determined by looking at the highest concentration of alpha-mangostin from each extraction time using TLC-densitometry method with a silica gel stationary phase of GF254 and a mobile phase of chloroform”methanol (10:0.1, v/v). Results: The results showed that the difference in the maceration time can affect the concentration of alpha-mangostin compound contained in the extract. Conclusions: It was found out that the 24-hour maceration time produced the highest concentration of alpha-mangostin that is 3031.34 ng.